Electrolyte and battery containing same
By introducing the first functional additive containing pyridine and ester groups into the electrolyte of the lithium-ion battery, the problem of poor circulation stability of the silicon negative electrode material is solved, and the improvement of battery circulation and rate performance is achieved.
Patent Information
- Application Number
- CN202411864450.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The cyclic stability of silicon negative electrode materials in lithium-ion batteries is not ideal, mainly due to stress caused by volume expansion, electrode plate cracking and SEI film breakage, which in turn affects the cyclic performance and rate performance of the battery.
An electrolyte containing a first functional additive of a specific structure is used, which forms a film on the positive and negative electrode side, promotes the stable growth of the SEI film and alleviates the silicon volume expansion effect. The additive contains pyridine and ester functional groups, which improves the chemical stability of the electrolyte and the migration efficiency of lithium ions.
It effectively improves the cycle performance and rate performance of silicon-based battery cells, enhances the stability of the SEI film, and reduces the negative impact of the volume change of silicon negative electrode on battery performance.
Smart Images

Figure CN119725720A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and specifically relates to an electrolyte and a battery containing the same. Background Art
[0002] Silicon material is recognized by the industry as the most promising negative electrode material for lithium-ion batteries. It has the following advantages: (1) extremely advantageous capacity. After complete alloying, silicon forms a Li-silicon alloy with a theoretical specific capacity of about 4200mAh / g; (2) low lithium deintercalation potential. When matched with the positive electrode, silicon has a higher output voltage at an operating potential of about 0.4V, showing a higher energy density. (3) extremely abundant reserves, good environmental compatibility, good environmental protection and electrochemical stability. The above advantages make silicon material one of the most promising materials for the new generation of high-performance battery negative electrode materials.
[0003] However, like all negative electrode materials for lithium storage by alloying mechanism, silicon also faces an unavoidable problem, namely, rapid volume expansion during the cycle, which leads to unsatisfactory cycle stability of silicon. During the alloying process, the volume of silicon-lithium alloy will expand to 3-4 times of the un-lithium-embedded state, and will shrink rapidly during the de-alloying process, which seriously restricts the application of silicon negative electrode.
[0004] During the lithiation and delithiation process, the large volume change of silicon is the primary reason for the rapid attenuation of battery capacity. The restricting mechanisms are mainly the following three points: (1) The large volume change causes huge stress inside the material. In the subsequent multiple cycles, the silicon particles gradually break or even pulverize; (2) With the continuous volume expansion and contraction of the cycle, most of the active materials lose electrical contact with adjacent active materials, the conductive agent network and the current collector, resulting in the "self-isolation" phenomenon of silicon materials, accompanied by cracking and breakage of the electrode plates, which significantly reduces the conductivity; (3) The volume change of silicon will cause the SEI film layer to break, and the fresh silicon surface will be exposed to the electrolyte, resulting in the continuous generation of the SEI film layer and the continuous consumption of the electrolyte. As the cycle process continues, a thick SEI film layer will cover the surface of the silicon particles.
[0005] Developing a new electrolyte that matches the silicon negative electrode is one of the effective means to improve the electrochemical performance of the silicon negative electrode. However, at this stage, commercial electrolytes are more suitable for graphite negative electrodes than silicon-based negative electrodes. This is mainly because organic solvents will be reduced and decomposed within the silicon lithiation voltage range. In addition, the volume of silicon changes, and each expansion will be accompanied by the decomposition of the electrolyte, thereby generating a thick SEI film at the interface, causing the electrode performance to decay rapidly. Therefore, the development of an electrolyte that is suitable for the lithium characteristics of the silicon negative electrode is of great significance to the electrochemical properties of silicon-based lithium batteries, such as cycle performance, rate performance, and energy density. Summary of the invention
[0006] In order to solve the problems and shortcomings existing in the prior art, the present application provides an electrolyte and a battery containing the same. In the electrolyte, it contains a first functional additive with a specific structure. The specific functional additive can form a film on the positive and negative electrode sides to promote the stability of the positive and negative electrodes. Especially for the silicon negative electrode, the specific functional additive promotes the stable growth of the SEI film on the negative electrode side, effectively alleviates the silicon volume expansion effect, and thus effectively improves the electrochemical properties of the battery, especially the cycle performance and rate performance of the silicon-based system battery.
[0007] According to the first aspect of the present application, an electrolyte is provided, comprising a lithium salt, an organic solvent, and a first functional additive; the structural formula of the first functional additive is:
[0008]
[0009] In the electrolyte of the present application, the first functional additive introduced contains pyridine and ester functional groups, which effectively improves the stability of the electrolyte and the electrochemical performance of the battery. First, the pyridine ring has certain aromaticity and conjugated structure, which can increase the chemical stability of the electrolyte, making it less likely to undergo redox decomposition reactions within the operating voltage range of the battery, and extending the service life of the electrolyte; the nitrogen atom in pyridine has lone pairs of electrons, which can interact with lithium ions, promote the dissociation and transmission of lithium ions, and improve the migration efficiency of lithium ions in the electrolyte, thereby improving the cycle performance and rate performance of the battery. Second, the ester group has a certain polarity, which can interact with solutes such as lithium salts in the electrolyte, helping the solutes to better dissolve and disperse in the electrolyte, thereby improving the ionic conductivity of the electrolyte, which is beneficial to the transmission of lithium ions in the electrolyte, and then improving the charge and discharge efficiency of the battery. Thirdly, both the pyridine ring and the ester group can react on the electrode surface, and the products thus obtained can participate in film formation on the positive and negative electrode sides, thereby improving the interface stability of the positive and negative electrodes. In particular, the SEI film formed with its participation can effectively alleviate the volume expansion effect of the silicon negative electrode, avoiding the exposure of the fresh silicon surface to the electrolyte and the continuous generation of the SEI film, which not only significantly improves the stability of the SEI film, but also greatly improves the stability of the silicon negative electrode material during the cycle process, thereby effectively improving the battery's electrochemical properties such as cycle performance and rate performance.
[0010] Preferably, in the first functional additive, R 1 , R 2 , R 3 , R 4 In the first functional additive, at least one is a halogen-containing substituent; the halogen includes at least one of F, Cl, Br, and I. 1 , R 2 , R 3 , R4 When at least one of the halogen-containing substituents is a halogen-containing substituent, halogen groups such as F, Cl, Br, and I can make the functional additives have stronger electron absorption capacity, thereby improving their antioxidant properties. In addition, halogen atoms may also participate in chemical reactions on the electrode surface, further promoting the formation of a stable SEI film, optimizing the stability of electrode materials and the cycle performance and rate performance of the battery. In addition, halogens also have high flame retardancy, which can further improve the safety performance of the battery.
[0011] Preferably, in the first functional additive, R 1 , R 2 , R 3 , R 4 Among them, at least two are halogen-containing substituents; the halogen includes at least one of F, Cl, Br, and I.
[0012] Preferably, in the first functional additive, R1 includes an oxygen-containing substituent, and the oxygen-containing substituent includes an ether-containing substituent or an alkoxy-containing substituent. The ether group and the alkoxy group have a certain polarity, and can interact with solutes such as lithium salts in the electrolyte, enhance the solubility of the first functional additive in the solvent, and make the various components in the electrolyte better mixed and even, thereby improving the overall performance of the electrolyte. At the same time, the oxygen atoms in the ether group and the alkoxy group can coordinate with lithium ions, participate in the solvation process of lithium ions, reduce the interaction force between lithium ions and anions, and help improve the transmission efficiency of lithium ions, improve ionic conductivity, and optimize battery rate performance. Moreover, the ether group and the alkoxy group can also further promote the stable formation of SEI film or CEI film, further reduce interface side reactions, optimize the stability of the positive and negative electrode interfaces, and further improve the cycle stability and service life of the battery.
[0013] Preferably, in the first functional additive, R 1 Including alkoxy or ether groups, R 2 Including at least one of F, Cl, Br, I, R 3 including hydrogen or an alkyl chain, R 4 Including at least one of F, Cl, Br, I, R 5 Preferably, in the first functional additive, R 1 Including methoxy, R 2 Including Br, R 3 Including hydrogen, R 4 Including Br, R 5 Including methyl.
[0014] Preferably, the relative molecular mass of the first functional additive is 150 to 400 g / mol. Controlling the relative molecular mass of the first functional additive within the above range is conducive to ensuring that it has relatively good solubility in the electrolyte and can also interact well with other components in the electrolyte, so that the electrolyte as a whole presents better performance and is more conducive to improving the overall performance of the battery.
[0015] Preferably, the mass proportion of the first functional additive in the electrolyte is 0.5-3wt%. The content of the first functional additive is controlled within the above range, firstly, to avoid the first functional additive with too little content having insufficient effect on the performance optimization of the electrolyte and the battery, and secondly, to avoid the first functional additive with too much content having a bad effect on other components in the electrolyte or affecting the interaction of the components in the electrolyte, deteriorating the overall performance of the electrolyte, and affecting the electrochemical properties such as the cycle performance and rate performance of the battery.
[0016] Preferably, the first functional additive includes 4,6-dibromo-3-methoxypyridine-2-carboxylic acid methyl ester, the structural formula of which is When the structural formula of the first functional additive is as above, the electrolyte formed by it and other components in the electrolyte has better stability and can promote the stable formation of the negative electrode SEI film, and can further promote the stable formation of the positive electrode CEI film, thereby further improving the cycle performance and rate performance of the battery. In particular, for the silicon negative electrode, the first functional additive under this structural formula can more significantly promote the formation of a stable SEI film, effectively alleviate the volume expansion problem of the silicon negative electrode, and thus effectively improve the electrochemical performance of the silicon-based system battery.
[0017] Preferably, the electrolyte further comprises a second functional additive, the second functional additive comprises a siloxane additive; the siloxane additive comprises at least one of tri(trimethylsilyl) borate (TMSB) and tri(trimethylsilyl) phosphate (TMSP). The above two siloxane additives have Si-O bonds, and the Si-O bonds can remove water and inhibit acid, so the stability of the SEI film and the CEI film can be further improved, the interface side reaction between the electrode material and the electrolyte can be reduced, the cycle stability of the electrode material can be improved, and the battery performance can be optimized. And the above two siloxane additives both reduce impedance to a certain extent, which is conducive to improving the battery rate performance.
[0018] Preferably, when the second functional additive includes a siloxane additive, the mass proportion of the second functional additive in the electrolyte is 0.2-4 wt %.
[0019] Preferably, the siloxane additive includes tri(trimethylsilyl) borate and tri(trimethylsilyl) phosphate. When the above two siloxane additives are contained at the same time, B atoms and P atoms are contained at the same time, which can further promote the stable formation of the negative electrode SEI film, while improving the lithium ion transmission performance, reducing the internal resistance of the battery, and optimizing the battery cycle performance and rate performance. At the same time, the electron-deficient B atom can complex the transition metal ions dissolved from the positive electrode during the charge and discharge process, improve the stability of the positive electrode, and thus be more conducive to further improving the overall performance of the battery.
[0020] Preferably, the mass proportion of tris(trimethylsilyl) borate in the electrolyte is 0.5-2wt%; the mass proportion of tris(trimethylsilyl) phosphate in the electrolyte is 0.2-1.5wt%.
[0021] Preferably, the organic solvent includes at least one of linear carbonate and cyclic carbonate.
[0022] Preferably, the linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and methyl propyl carbonate.
[0023] Preferably, the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate, and propylene carbonate.
[0024] Preferably, the organic solvent comprises linear carbonate and cyclic carbonate. Preferably, the volume ratio of linear carbonate to cyclic carbonate is 60-80:20-40.
[0025] Preferably, the organic solvent includes diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, and vinyl carbonate, and the volume ratio of diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, and vinyl carbonate is 15 to 40: 5 to 80: 10 to 30: 30 to 60. Preferably, the volume ratio of diethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, and vinyl carbonate is 25: 12: 18: 45.
[0026] Preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl imide) salt, and lithium bis(oxalatoborate).
[0027] Preferably, the concentration of lithium salt in the electrolyte is 1 to 1.5 mol / L.
[0028] According to the second battery of the present application, the electrolyte is included. The battery prepared by using the electrolyte has effectively improved cycle performance and rate performance. Especially for batteries with silicon-based negative electrode systems, the improvement effect is more obvious. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present application, rather than all of the embodiments.
[0030] Example 1
[0031] 1. Composition and preparation of electrolyte
[0032] The electrolyte in this embodiment includes lithium salt, organic solvent, a first functional additive, and a second functional additive.
[0033] Lithium salts include lithium hexafluorophosphate (LiPF 6 ), and the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L.
[0034] The first functional additive is methyl 4,6-dibromo-3-methoxypyridine-2-carboxylate, and its mass proportion in the electrolyte is 1.7wt%. The second functional additive includes tris(trimethylsilyl) borate (TMSB) and tris(trimethylsilyl) phosphate (TMSP), and the mass proportion of tris(trimethylsilyl) borate in the electrolyte is 1.3wt%, and the mass proportion of tris(trimethylsilyl) phosphate in the electrolyte is 0.8wt%.
[0035] The organic solvent includes diethyl carbonate (DEC), fluoroethylene carbonate (FEC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC), and the volume ratio of diethyl carbonate, fluoroethylene carbonate, ethylene carbonate, and ethyl methyl carbonate is 25:12:18:45.
[0036] The preparation of the electrolyte is carried out according to the following steps: in an argon atmosphere, the lithium salt, functional additives and film-forming additives are mixed evenly in an organic solvent, and stirred at low temperature during the mixing process.
[0037] 2. Preparation of batteries
[0038] Preparation of lithium-ion batteries
[0039] (1) Preparation of positive electrode
[0040] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O 2 ) The positive electrode active material, binder PVDF (polyvinylidene fluoride), and conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain a positive electrode slurry, and then the positive electrode slurry is coated on an aluminum foil through a coating process, and a positive electrode sheet is obtained after vacuum drying and cold pressing processes.
[0041] (2) Preparation of negative electrode
[0042] Silicon-carbon negative electrode material (silicon content is 40-60wt%), conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain a negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on a copper foil through a coating process, and a negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0043] (3) Selection of electrolyte
[0044] The electrolyte prepared in this example is used.
[0045] (4) Selection of isolation membrane
[0046] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0047] (5) Preparation of lithium-ion batteries
[0048] The positive electrode sheet, separator and negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The bare battery cell is placed in an outer packaging shell, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first functional additive is adjusted to 3-methoxypyridine-2-carboxylic acid methyl ester, the structural formula of which is The rest is consistent with Example 1.
[0051] Example 3
[0052] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first functional additive is adjusted to The rest is consistent with Example 1.
[0053] Example 4
[0054] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first functional additive is adjusted to 4,6-dichloro-3-methoxypicolinic acid methyl ester, whose structural formula is The rest is consistent with Example 1.
[0055] Example 5
[0056] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first functional additive is adjusted to 4,6-dibromopicolinic acid methyl ester, whose structural formula is The rest is consistent with Example 1.
[0057] Example 6
[0058] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first functional additive is adjusted to 4,6-dibromo-3-hydroxypicolinic acid methyl ester, whose structural formula is The rest is consistent with Example 1.
[0059] Example 7
[0060] The difference between this embodiment and embodiment 1 is that in the prepared electrolyte, the first functional additive is adjusted to The rest is consistent with Example 1.
[0061] Example 8
[0062] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the first functional additive in the electrolyte is adjusted to 0.3 wt %; the rest is consistent with embodiment 1.
[0063] Example 9
[0064] The difference between this embodiment and embodiment 1 is that, in the prepared electrolyte, the mass proportion of the first functional additive in the electrolyte is adjusted to 3.5wt%; the rest is consistent with embodiment 1.
[0065] Example 10
[0066] This embodiment is different from Embodiment 1 in that tri(trimethylsilyl) phosphate is not added to the prepared electrolyte, that is, the second functional additive contains only tri(trimethylsilyl) borate, and its mass proportion in the electrolyte is 1.3wt%; the rest is consistent with Embodiment 1.
[0067] Embodiment 11
[0068] The difference between this embodiment and embodiment 1 is that tri(trimethylsilyl) borate is not added to the prepared electrolyte, that is, the second functional additive contains only tri(trimethylsilyl) phosphate, and its mass proportion in the electrolyte is 0.8wt%; the rest is consistent with embodiment 1.
[0069] Example 12
[0070] This embodiment is different from Embodiment 1 in that the second functional additive is not added to the prepared electrolyte, that is, tri(trimethylsilyl) borate (TMSB) and tri(trimethylsilyl) phosphate (TMSP) are not added; the rest is the same as Embodiment 1.
[0071] Embodiment 13
[0072] This embodiment is different from Embodiment 1 in that, in the prepared electrolyte, no diethyl carbonate (DEC) is added to the organic solvent, and the volume ratio of fluoroethylene carbonate, ethylene carbonate, and ethyl methyl carbonate is 12:18:45; the rest is consistent with Embodiment 1.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that the prepared electrolyte does not contain the first functional additive, that is, does not contain 4,6-dibromo-3-methoxypyridine-2-carboxylic acid methyl ester; the rest is consistent with Example 1. .
[0075] Comparative Example 2
[0076] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the first functional additive is adjusted to The rest is consistent with Example 1.
[0077] Comparative Example 3
[0078] The difference between this comparative example and Example 1 is that in the prepared electrolyte, the first functional additive is adjusted to The rest is consistent with Example 1.
[0079] Test Case
[0080] 1. Experimental Construction Method
[0081] The batteries prepared in all the above examples and comparative examples were tested on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. at room temperature (25°C), and the charge and discharge voltage was limited to 2.5V to 4.2V. The test methods for the first efficiency, cycle and rate performance are as follows:
[0082] 1) First Coulomb efficiency
[0083] At 25°C, the battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, left to stand for 10 minutes, and then discharged to 2.5V at a constant current rate of 0.33C, left to stand for 10 minutes, and the first coulombic efficiency of the battery was calculated.
[0084] First coulombic efficiency (%) = total capacity of the battery at the first discharge at 0.33C / total capacity of the battery at the first charge at 0.33C × 100%.
[0085] 2) Capacity retention rate after 1000 cycles at 1C / 1C at room temperature
[0086] At 25°C, the battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the battery is discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This is considered one charge and discharge cycle. The battery is charged and discharged for 1000 cycles according to the above method, and the capacity retention rate after 1000 cycles of charge and discharge at 1C / 1C is calculated.
[0087] The capacity retention rate (%) of the battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the battery.
[0088] 3) Capacity retention rate at high temperature 45℃ 1C / 1C cycle for 1000 cycles
[0089] At 45°C, the battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the battery was discharged to 2.5V at a constant current rate of 1C and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate after 1000 cycles of charge and discharge at 1C / 1C was calculated.
[0090] The capacity retention rate (%) of the battery after N cycles = (discharge capacity at the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the battery.
[0091] 4) Room temperature 6C rate performance - constant current charging ratio
[0092] At 25°C, the battery was discharged at a constant current rate of 1C to 2.5V and allowed to stand for 10 minutes. Then, the battery was charged at a constant current and constant voltage rate of 6C to 4.2V with a cut-off current of 0.05C. The battery was allowed to stand for 10 minutes. The constant current charging capacity Q1 and the constant current and constant voltage charging total capacity Q2 of the battery were recorded. The 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = constant current charging capacity Q1 / constant current and constant voltage charging total capacity Q2 × 100%.
[0093] 2. Experimental results
[0094] The relevant performance test results of the batteries prepared in all the above embodiments and comparative examples are shown in Table 1.
[0095] Table 1 Related performance test results of batteries prepared in Examples and Comparative Examples
[0096]
[0097] As can be seen from Table 1, the battery prepared using the electrolyte provided by the present application has good performance in terms of initial efficiency, normal temperature and high temperature cycle performance, and 6C constant current charging ratio. This is because the electrolyte provided by the present application, especially the first functional additive introduced, can form a film on the positive and negative electrode sides, promote the stability of the positive and negative electrodes, especially for the silicon negative electrode. The specific functional additive promotes the stable growth of the SEI film on the negative electrode side, effectively alleviates the silicon volume expansion effect, and thus effectively improves the battery, especially the silicon-based system battery. Electrochemical properties such as cycle performance and rate performance. Specific reference to Examples 1 to 13. Comparative Example 1 does not contain the first functional additive, the first functional additive in Comparative Example 2 does not contain an ester group, and the first functional additive in Comparative Example 3 does not contain a pyridine ring (a benzene ring), all of which lead to a decrease in the performance of the battery in various aspects. This shows that the first functional additive plays a key role in improving the performance of the electrolyte. At the same time, changes in some groups in the first functional additive will have a significant impact on the performance of the first functional additive, resulting in a significant decrease in the performance of the electrolyte composed of the first functional additive, and cannot effectively improve the interface stability of the negative electrode and the positive electrode and alleviate the volume expansion of the silicon negative electrode, ultimately causing the battery performance to deteriorate.
[0098] Further comparing Example 1 with Examples 2 to 6, there is no halogen substituent in the substituent in the first functional additive in Example 2, there is only one halogen substituent (Br) in the substituent in the first functional additive in Example 3, there are two Cl substituents in the substituent in the first functional additive in Example 4, and R in the first functional additive in Example 5 1 The above changes all lead to a decrease in the performance of the batteries in Examples 2 to 6. Further comparison of Examples 2 to 4 shows that the battery performance in Example 3 is better than that in Example 2, and the battery performance in Example 4 is better than that in Examples 2 to 3, which indicates that the presence of two Br halogen substituents is more conducive to optimizing the performance of the electrolyte, thereby further improving the performance of the battery.
[0099] Comparing Example 1 with Examples 8 and 9, the first functional additive in Examples 8 and 9 is too little and too much, respectively, resulting in a decrease in the performance of the batteries in Examples 8 and 9. This indicates that controlling the addition amount of the first functional additive within a specific range is more conducive to the overall performance of the electrolyte, thereby further optimizing the performance of the battery.
[0100] Comparing Example 1 with Examples 10 to 12, in Example 10, the second functional additive only contains tri(trimethylsilyl) borate, in Example 11, the second functional additive only contains tri(trimethylsilyl) phosphate, and in Example 12, no second functional additive is included, resulting in a decrease in the performance of the batteries in Examples 10 to 12, especially in Example 12. This shows that the use of the first functional additive and the second functional additive together is more conducive to exerting the improvement effect of the electrolyte on the battery, thereby further optimizing the performance of the battery.
[0101] Comparing Example 1 and Example 13, in Example 13, diethyl carbonate (DEC) is not added to the organic solvent, which may reduce the interaction effect of the solute in the solvent, thereby reducing the overall performance of the electrolyte, and ultimately leading to a decrease in battery performance.
[0102] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. An electrolyte, characterized in that: Including lithium salt, organic solvent, and first functional additive; The structural formula of the first functional additive is:
2. The electrolyte according to claim 1, characterized in that: In the first functional additive, at least one of R1, R2, R3, and R4 is a halogen-containing substituent; the halogen includes at least one of F, Cl, Br, and I.
3. The electrolyte according to claim 2, characterized in that: In the first functional additive, R1 includes an oxygen-containing substituent, and the oxygen-containing substituent includes an ether-containing substituent or an alkoxy-containing substituent.
4. The electrolyte according to claim 1, characterized in that: The relative molecular mass of the first functional additive is 150-400 g / mol; the mass proportion of the first functional additive in the electrolyte is 0.5-3 wt %.
5. The electrolyte according to claim 1, characterized in that: The first functional additive includes 4,6-dibromo-3-methoxypyridine-2-carboxylic acid methyl ester, and its structural formula is 6. The electrolyte according to claim 1, characterized in that: Also included is a second functional additive, wherein the second functional additive includes a siloxane additive; the siloxane additive includes at least one of tris(trimethylsilyl) borate and tris(trimethylsilyl) phosphate; The mass percentage of the second functional additive in the electrolyte is 0.2-4 wt %.
7. The electrolyte according to claim 6, characterized in that: The siloxane additives include tris(trimethylsilyl) borate and tris(trimethylsilyl) phosphate; The mass percentage of tri(trimethylsilyl) borate in the electrolyte is 0.5-2wt%; The mass proportion of tris(trimethylsilyl)phosphate in the electrolyte is 0.2-1.5 wt %.
8. The electrolyte according to claim 1, characterized in that: The organic solvent includes at least one of a linear carbonate and a cyclic carbonate; The linear carbonate comprises at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; The cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.
9. The electrolyte according to claim 1, characterized in that: The lithium salt includes at least one of lithium hexafluorophosphate, lithium trifluoromethanesulfonyl imide, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl imide) salt, and lithium bis(oxalate) borate; The concentration of the lithium salt in the electrolyte is 1 to 1.5 mol / L.
10. A battery, characterized in that: Comprising the electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion battery electrolyte and lithium ion battery using same
CN105845984A
High-voltage lithium ion battery combined electrolyte additive, electrolyte and battery thereof
CN110943253A
High-voltage lithium ion battery electrolyte additive, electrolyte, battery and formation method thereof
CN111244543A
Electrolyte for high-power lithium battery and preparation method of electrolyte
CN111261941A
Lithium ion battery electrolyte additive, electrolyte and lithium ion battery
CN114361590A